The Effect of Company Competition, Company Size and Environmental Performance on Carbon Emissions Disclosure - Saputri, Septiana Dwi; Astuti, Sri; Sandhi, Indah Kartika (AIBPM Publisher, 2023)
This study aims to determine whether or not there is an effect of company competition, company size, and environmental performance on disclosure of carbon emissions. This research was conducted on energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period, totaling 237 companies obtained by purposive sampling. The method of analysis in this study is multiple regression analysis with IBM SPSS Statistics 26 software to test the variables of company competition, company size, and environmental performance on carbon emissions disclosure. The results of this study indicate that partially company competition have no effect on disclosure of carbon emissions. While company size and environmental performance affects the disclosure of carbon emissions. Simultaneously, company competition, company size, and environmental performance together affect the disclosure of carbon emissions.